Engineering the Multi-Length Scale Structure of Self-Assembled Conjugated Polymer Networks - Newbloom, Gregory Matthew (My University, 2014)
Conjugated polymers are a Nobel Prize winning class of materials known for their intrinsic semi-conducting properties and have been used in applications as diverse as organic-based solar cells, transistors, light emitting diodes, sensors and thermoelectric devices. These applications have varying, but optimized, structure and property requirements which often include an interconnected network of conjugated polymers to transport charge. In this work, self-assembly and gelation are explored as a platform to engineer the multi-length scale structure of conjugated polymer networks. A detailed understanding is developed through structural characterization of each stage of the self-assembly process: dissolved polymer, semi-crystalline fiber, fibrillar branching and percolated network formation. Variations in self-assembly conditions were utilized to develop multi-length scale structure-property relationships. Furthermore, a new method to directly incorporate these fibrillar network structures into thin films for organic electronics is discussed. This dissertation will demonstrate our work towards understanding the mechanisms behind conjugated polymer self-assembly in order to provide robust design parameters that can be tuned to generate specific structures, occurring on multiple length scales, and relevant properties for a diversity of applications.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Conjugated Polymer; Multi-Length Scale; Neutron Scattering; Organic Electronics; Self-Assembly; Chemical engineering; chemical engineering